Molecular docking study of naturally derived β-mangostin with antiapoptotic Bcl-2 proteins toward oral cancer treatment / Mohamad Zakkirun Abdullah ... [et al.] - Abdullah, Mohamad Zakkirun; Bakar, Latifah Munirah; Arief Ichwan, Solachuddin Jauhari; Othman, Noratikah; Taher, Muhammad (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Targeting the apoptosis-inducing pathway has drawn much attention in searching for a novel anticancer drug. Bcl-2 is the most studied antiapoptotic protein, recognised in aiding in cell survival and overexpressed in most cancer cells resulting in cancer resistance toward conventional treatment. The inhibition of Bcl-2 proteins become the main target for inducing apoptosis in cancer cells. β-mangostin received minimum attention in investigating anticancer properties as compared to its family such αmangostin. We performed molecular docking of β-mangostin, doxorubicin (in silico control) and ABT-737 (co-crystal Bcl-2 inhibitor) against antiapoptotic Bcl-2 protein using PyMol, Discovery Studio Biovia 2021, AutoDock Vina, and AutoDock Tools version 1.5.7. The result demonstrates for the first time that β-mangostin showed an optimum binding affinity with Bcl-2 (∆G −7.3 kcal/mol), similar to those shown by doxorubicin. The present results indicate that β-mangostin could potentially serve as Bcl-2 protein inhibitors, which would consequently lead to an apoptotic process in oral cancers. The present data warrant validation using in vitro and in vivo assays.